Tagus estuary and Ria de Aveiro salt marsh dynamics and the impact of sea level rise - Valentim, J. M. (2018)
Different characteristics of Spartina maritima found in two distinct salt marshes located in different estuaries were analysed through interpretation of their local hydrodynamic patterns, as well as the impact of sea level rise on physical processes and consequently on plant dynamics and salt marshes stability. These salt marshes are situated in two of the most important Portuguese coastal systems, Tagus estuary (Rosário salt marsh) and Ria de Aveiro lagoon (Barra salt marsh), which are dominated by physical processes that induce strong tidal currents. They were monitored during one year and plant and sediment samples of S.maritima were collected quarterly in order to determine the vegetation coverage, above and belowground biomass, organic matter and sediment moisture. Residual circulation, tidal asymmetry and tidal dissipation were determined from numerical modelling results of the MOHID 2D model that was applied to each coastal system, considering the actual sea level and a sea level rise (SLR) scenario.Results suggest that the different characteristics found for Spartina maritima in the Rosário and the Barra salt marshes may be related with the diverse hydrodynamic conditions identified for each salt marsh. Consequently, the exploration of SLR scenario predictions indicates how these salt marshes could evolve in the future, showing that the important changes in these hydrodynamic parameters under climate change context might induce significant modifications in the salt marshes dynamics and stability. SLR scenario could lead to changes in nutrients and sediments patterns around the salt marshes and thus vegetation coverage percentage would be affected. Additionally, as a consequence of flood duration increase, sediment moisture will increase causing a stress condition to plants. Hence, the ratio below/aboveground biomass might increase, becoming critical to plants survival under conditions of accelerated sea level rise. Accordingly, both SLR and expected changes in vegetation coverage percentage in controlling salt marshes evolution have important implications in their stability and consequently in coastal management. These conditions are unlikely to be unique to these salt marshes and it is suggested that similar analyses are replicated for other tidally dominated systems to improve understanding and characterization of their dynamics and stability under climate change context.